การพัฒนารูปแบบธุรกิจชุมชนอย่างยั่งยืน กรณีศึกษา กลุ่มผักปลอดสารบ้านดอนสถาน อำเภอปัว จังหวัดน่าน / The Development of a Sustainable Community Enterprise Model: A Case Study of the Puk Plod San Ban Don Satan Group in Pua District, Nan Province - Thammajinda, Rojana; Chingchayanurak, Chanon; Jitaree, Wisutorn; Trakarnsirinont, Worraphan; Navaratana na Ayudhya, Theerakiti (Journal of Community Development Research (Humanities and Social Sciences); Vol 10 No 4 (2560): October-December 2017, 2017)
การวิจัยนี้เป็นการวิจัยเชิงปฏิบัติการแบบมีส่วนร่วม มีวัตถุประสงค์เพื่อศึกษากระบวนการในการพัฒนาอย่างยั่งยืน โดยการมีส่วนร่วมของชุมชน และเพื่อค้นหารูปแบบการรวมกลุ่มธุรกิจชุมชนอย่างยั่งยืน โดยศึกษาประชากรสมาชิกกลุ่มผักปลอดสารบ้านดอนสถาน และผู้นำชุมชน จำนวน 13 คน เครื่องมือที่ใช้ในการศึกษา คือ การสัมภาษณ์ การสังเกตการณ์แบบมีส่วนร่วม การนำชาวบ้านไปศึกษาดูงาน การสนทนากลุ่มและการประชุมกลุ่ม ระยะเวลาในการศึกษาตั้งแต่ตุลาคม 2558 ถึงตุลาคม 2559 ผลการวิจัย พบว่า กระบวนการพัฒนาชุมชนอย่างยั่งยืนโดยการมีส่วนร่วม มี 7 ขั้นตอน คือ 1. การแนะนำนักวิจัยและแจ้งวัตถุประสงค์การวิจัยให้กับชุมชน 2. การร่วมกันศึกษาและวิเคราะห์ปัญหาชุมชน 3. การเติมองค์ความรู้ให้ชุมชน 4. การร่วมกันพิจารณารูปแบบการพัฒนาที่เหมาะสมและมีความเป็นไปได้ 5. การร่วมกันวางแผนการดำเนินงาน 6. การปฏิบัติตามแผน และ 7. การติดตามและประเมินผล รูปแบบการรวมกลุ่มธุรกิจชุมชนผักปลอดสารบ้านดอนสถานมีรูปแบบเฉพาะที่แตกต่างจากชุมชนอื่น กล่าวคือ มีการรวมกลุ่มเพื่อผลิตผักปลอดสาร ควบคุมคุณภาพ และจำหน่ายผักปลอดสารในนามกลุ่มฯ ลักษณะการร่วมทุนประกอบไปด้วยทุนส่วนรวมและทุนส่วนตัว การจัดตั้งกลุ่มธุรกิจชุมชนนี้ทำให้สมาชิกสามารถขายผลผลิตในราคาที่เป็นธรรมมากขึ้น ลดการพึ่งพาพ่อค้าคนกลาง ลดการใช้สารเคมีในการเพาะปลูก ซึ่งเป็นผลดีทั้งต่อสุขภาพของเกษตรกรและสภาพแวดล้อม ข้อเสนอแนะจากงานวิจัย คือ สมาชิกกลุ่มผักปลอดสารบ้านดอนสถานควรจัดทำแผนการตลาดและแผนการผลิตเพื่อรองรับการขยายตลาดต่อไป      This participatory action research (PAR) studies the sustainable development through a community participation process and searches for a sustainable community enterprise model. The research is conducted from October 2015 to October 2016 and has 13 informants, including group members and community leaders. The methodologies used include in-depth interviews, participatory observation, visits with successful communities, and focus group meetings. The research results demonstrate the seven steps in sustainable development community participation processes. 1 Introduce research team and objectives, 2 Study and analyze community problems, 3 Fill the knowledge gap to local residents, 4 Search for a suitable model of community enterprise, 5 Develop action plan, 6 Implementation, and 7 Follow up and evaluation. The study finds that the community enterprise model of Ban Don Satan may be different from those used in other communities. This group aims to produce, control and sell organic vegetables. Funding for their operations includes both collective and individual funds. Establishing a Community enterprise may result in many benefits such as fair product prices, less dependence on middlemen, and less use of harmful chemicals, resulting in better health and an improved environment for the farmers. This research suggests that the members of “Puk Plod San Ban Don Satan” group should do marketing and production plan for market expansion.
Keywords: Sustainable community enterprise